2016
DOI: 10.1159/000447961
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mechanics in Patients with Abnormal Origin of the Left Main Coronary Artery from the Pulmonary Trunk Late after Successful Repair

Abstract: Objective: Our aim was to evaluate left ventricular (LV) mechanics by using speckle tracking echocardiography (STE) in asymptomatic patients with abnormal origin of the left main coronary artery from the pulmonary trunk (ALCAPA), late after successful repair, in the presence of LV ejection fraction (EF) >50%. Methods: We studied 30 ALCAPA patients (median age 4 years, range 1-25 years, NYHA class I, LVEF >50%) and 16 healthy age- and sex-matched controls (median age 5 years, range 1-25 years). All underwent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
10
1
3
Order By: Relevance
“…In the study by Secinaro et al [31] performed with the use of the cardiac magnetic resonance imaging in 6 patients aged 6–21 years, the abnormalities were localized in the LV antero-lateral wall. In our study, the impaired LS was located predominantly in the LV postero-lateral wall, however in contrast to other studies [9,11, 30] regional abnormalities were present also in the RCA region. Additionally, some authors [16, 31] observed sparing of the apical segments after ALCAPA repair, while patients in our study showed akinetic apical segments and severely abnormal LS in this region.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the study by Secinaro et al [31] performed with the use of the cardiac magnetic resonance imaging in 6 patients aged 6–21 years, the abnormalities were localized in the LV antero-lateral wall. In our study, the impaired LS was located predominantly in the LV postero-lateral wall, however in contrast to other studies [9,11, 30] regional abnormalities were present also in the RCA region. Additionally, some authors [16, 31] observed sparing of the apical segments after ALCAPA repair, while patients in our study showed akinetic apical segments and severely abnormal LS in this region.…”
Section: Discussioncontrasting
confidence: 99%
“…Mertens et al reported on the utility of serial strain measurements in an infant after ALCAPA repair, in who after the surgery the recovery of longitudinal function was delayed when compared with radial function [29]. Similarly, Di Salvo et al [30] showed persistent abnormal longitudinal myocardial strain in 30 patients assessed at least 12 months after ALCAPA repair. In contrast, Cabrera et al [9] showed decreased both: global longitudinal and circumferential strain in 11 out of 14 ALCAPA patients (79%) examined at (median) 6 years after surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, ALCAPA was present in 0.42% of patients while in the largest series of CAAs, ALCAPA was present in 0.95% [13]. These patients often have an impaired cardiovascular mechanics with one of the studies reporting impaired left ventricular (LV) longitudinal deformation and LV torsion along with diastolic dysfunction following surgery in asymptomatic ALCAPA with normal global systolic function (LVEF >50%) [20].…”
Section: Discussionmentioning
confidence: 55%
“…LV dysfunction has been reported as the main risk factor for perioperative mortality [18,19]. We have observed that there is the minimal improvement in LVEF on the day of surgery.…”
Section: Left Ventricular Functionmentioning
confidence: 73%
“…Medical practitioners generally believe that with the improvement of LV function and dimensions after successful revascularisation, the mitral annular size shall decrease with subsequent improvement in MR. However, our experience does not corroborate this view point, and for patients who come in late infancy and childhood with severe MR, where the cause of MR is ischemic lesions of the papillary muscle (organic MR), we recommend MV repair [18,19]. In this group, mitral annuloplasty in association with coronary reimplantation is indicated due to the reduced likelihood of regression of MR after coronary revascularisation [26].…”
Section: Mitral Regurgitationmentioning
confidence: 82%